The antinociceptive effect of Carica Papaya L. leaf aqueous extract in mice - Mohd Hafez Bahadom (2012, 2012)
Papaya or Carica papaya L. is a type of herbaceous plant that is widely distributed around the world mainly in the tropic and subtropic regions. It is a large perennial herb with a rapid growth rate and interstingly, the male and female parts exist in different trees. The different part of Carica papaya L. such as fruit/pulp, leaves, seed, flower, latex and root are used as traditional medicine in different countries around the world. Recent studies showed that papaya leaves possess antitumor and anti-inflammatory properties but no scientific studies were carried out to assess the possibility of papaya leaf as a potential analgesic agent. This study was conducted to investigate the antinociceptive property of papaya leaf aqueous extract (CPLE) in mice. This analgesic activity of CPLE was evaluated using the acetic acid-induced writhing test while the effect of extract on motor coordination and balance was assessed using Rotarod performance test. Results showed that intraperitoneal administration of extract (30, 100 and 300 mg/kg) significantly reduced the number of abdominal constrictions without disturbing motor performance and balanced in mice. In conclusion, Carica papaya L. leaf aqueous extract possesses antinociceptive activity by acting through the peripheral nervous system without altering the motor coordination and balance in mice.
Project paper (D.V.M) - Universiti Putra Malaysia, 2012.